2004
DOI: 10.1152/ajpheart.00221.2004
|View full text |Cite
|
Sign up to set email alerts
|

Unequal effects of renin-angiotensin system inhibitors in acute cardiac dysfunction induced by isoproterenol

Abstract: Several clinical trials have demonstrated that angiotensin-converting enzyme inhibitor (ACEI) and angiotensin II type 1 receptor blocker (ARB) are equally effective in the treatment of chronic heart failure. However, this has not been confirmed for acute cardiac dysfunction. We examined whether ACEI or ARB prevents isoproterenol-induced acute left ventricular (LV) dysfunction in dogs. LV dysfunction induced by a large dose of isoproterenol (1 microg.kg(-1).min(-1), 3-h infusion) was compared in dogs treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…The pharmacological mechanism is that ARBs have direct effect via dilatation of arteries and veins and thereby results in reduction in preload and afterload and hence subsequent decrease in LVEDP [1,5,8]. In corroboration with our findings Ohta et al have also demonstrated that ARBs restored cardiac dysfunction induced by ISO [22]. Lipid peroxidation plays an important role in the pathogenesis of MI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The pharmacological mechanism is that ARBs have direct effect via dilatation of arteries and veins and thereby results in reduction in preload and afterload and hence subsequent decrease in LVEDP [1,5,8]. In corroboration with our findings Ohta et al have also demonstrated that ARBs restored cardiac dysfunction induced by ISO [22]. Lipid peroxidation plays an important role in the pathogenesis of MI.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, ARBs also inhibit cardiac and vascular remodeling associated with chronic hypertension and MI thereby suggesting a protective role in myocardial injury [7,8]. In consonance with our findings various experimental studies have also reported beneficial effects of AT1 antagonists in myocardial infarction in rats [21][22][23]. However, no significant alterations were observed in heart rate, among all groups.…”
Section: Discussionsupporting
confidence: 87%
“…The ISO loading dose was determined from both a preliminary study and previous study using the same experimental model (31). As the maximal dose, one which did not induce crucial hemodynamic deterioration or fatal arrhythmias during more than 4 h of experiments, 1 g ⅐ kg Ϫ1 ⅐ min Ϫ1 of ISO was selected.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…To achieve this goal, we used an ISO-induced cardiac dysfunction and ␤-adrenergic desensitization dog model (31).…”
mentioning
confidence: 99%
“…In 1983, however, one did not know about the five different dopamine receptor subtypes, so re-examination of this question with receptor-knockout models and/or improved pharmacological agents may be worthwhile. In addition, the role of G␣ selectivity in the novel pharmacology of aripiprazole (Ohta et al, 2004) will be of interest to study. Second, distinct effector mechanisms have been proposed for G i and G o signaling, activation of G protein-coupled inwardly rectifying potassium channel currents, and inhibition of voltage-gated Ca 2ϩ channels (Sowell et al, 1997;Valenzuela et al, 1997).…”
mentioning
confidence: 99%